Physiology, Taxonomy, and Sulfur Metabolism of the Sulfolobales, an Order of Thermoacidophilic Archaea - Liu, Li-Jun; Jiang, Zhen; Wang, Pei; Qin, Ya-Ling; Xu, Wen; Wang, Yang; Liu, Shuang-Jiang; Jiang, Cheng-Ying (Frontiers in Microbiology, 2021)
The order Sulfolobales (phylum Crenarchaeota) is a group of thermoacidophilic archaea. The first member of the Sulfolobales was discovered in 1972, and current 23 species are validly named under the International Code of Nomenclature of Prokaryotes. The majority of members of the Sulfolobales are obligately or facultatively chemolithoautotrophic. When they grow autotrophically, elemental sulfur or reduced inorganic sulfur compounds are their energy sources. Therefore, sulfur metabolism is the most important physiological characteristic of the Sulfolobales. The functions of some enzymes and proteins involved in sulfur reduction, sulfur oxidation, sulfide oxidation, thiosulfate oxidation, sulfite oxidation, tetrathionate hydrolysis, and sulfur trafficking have been determined. In this review, we describe current knowledge about the physiology, taxonomy and sulfur metabolism of the Sulfolobales, and note future challenges in this field.